Print reading for architecture and construction technology - Madsen, David; Madsen, David A. (Clifton Park, NY : Delmar, Cengage Learning, 2013)
Print Reading for Architecture and Construction Technology provides the knowledge and skills required to accurately read blueprints for residential and light commercial construction. This easy-to-use text explores all print reading applications, with examples and illustrations taken from actual architectural prints. Students are provided with the information they need to read high-quality, standardized'real world' prints of working drawings. In addition, this edition is fully updated with CADD-generated print reading examples, illustrations, and exercises that comply with the highest industry standards.--COVER.
Introduction to architecture and construction technology print reading -- Reading site plans -- Reading floor plans, part 1 : Floor plan symbols -- Reading floor plans, part 2 : Floor plan dimensions -- Reading floor plans, part 3 : Electrical, plumbing, and HVAC -- Reading elevations -- Reading millwork details and cabinet elevations -- Reading framing methods, structural components, and framing plans -- Reading proof-related drawings -- Foundation and floor systems -- Reading sections and details -- Reading stair drawings -- Reading fireplace drawings -- Construction specifications and energy-efficient construction applications -- App. A. Metric in construction -- App. B. Thermal calculations for heating/cooling.
Includes index.
Keywords: Building -- Details -- Drawings; Blueprints; Architecture -- Designs and plans